Challenges and prospects in the public health research system in the occupied Palestinian territory: a qualitative study. (21st February 2018) - Al Khaldi, Mohammed; Abed, Yehia; Alkaiyat, Abdulsalam; Tanner, Marcel
Abstract: Background: A public health research system is the bedrock of health systems to improve population health, system responsiveness, and equity. An international concern, referred to as the 10/90 gap, is that less than 10% of global funds are devoted to diseases or conditions that account for 90% of the global disease burden, particularly in developing countries. Palestinian health research is progressing, but it is not sufficiently investigated, with a remarkable knowledge gap on its conceptualisation, stewardship, stakeholders, and capacity and resources. The aim of this study was to understand the Palestinian public health research system by investigating challenges related to the system components that need to be strengthened. Methods: The study was done in the Gaza Strip and West Bank in the occupied Palestinian territory between January and July, 2016. We targeted relevant government institutions, academic schools, and large local and international health agencies. Data were collected through 52 in-depth interviews and six focus group discussions with policy makers, academics, and experts. Participants and institutions were selected purposively on the basis of stated criteria and peer review. Data were translated, transcribed, checked, and imported into MAXQDA 12 for thematic and content analysis. Approvals were obtained from The Research Commission of Swiss TPH, "Ethikkommission Nordwest- und Zentralschweiz" (EKNZ) in Switzerland, the Palestinian Ministry of Health, Helsinki Committee, and An-Najah National University in Palestine. Findings: The health research system is not well structured, whereas public health research is promising but probably without regulated national policies. Most experts emphasised that governance is not clearly framed in managing research functions, whereas public health research activities are most likely scattered and individually driven. There is a consensus that the concept of the health research system is misunderstood and that the system is underperforming because of various problems such as resource insufficiency. Research is also not fundamentally at the heart of the political agenda or itemised in central budgets. Besides workforce scarcity with poor incentives and infrastructure, priorities in public health research are inconsistent and efforts are uncoordinated with poor multidisciplinary research. Dissemination and application of the public health research agenda among stakeholders are lacking. The research culture seems to be insufficiently cultivated. The international support to the public health research system is inconspicuous although some initiatives have been successful. The overall environment in the occupied Palestinian territory formed one of obstacles of the public health research system. Precious opportunities are proposed to strengthen public health research system synergistically through best strategies. Interpretation: The occupied Palestinian territory is a fertile place for growth of public health research system activity. Development actions should therefore be taken to get the system materialised by reactivating a unified governance body that cooperatively manages the national policies, capacities, priorities, research utilisation, and application of the public health research system. Funding: The Swiss Federation and Swiss Tropical and Public Health Institute.